SEXUALITY IN PRISON: A STUDY ON PRISONER’S BIOLOGICAL NEED FROM A HUMAN RIGHTS PERSPECTIVE - Harison Citrawan (Pusbindiklat - LIPI, 2013)
Prisoner’s sexual need has been long a major discourse in Indonesia’s national correctional system. Up to this day, such a need is yet to be ruled under any legislative products. It is fully undoubted that the absence of legal protection upon prisoner’s sexual need may cause several negative impacts, such as sexual harassment, emotional instability, and to a certain extent family brake-ups. This research aims to discern the contstruction of prisoner’s sexual need as a right from a human rights perspective, and attempts to construe a proportional mechanism in fulfilling the right. The author used qualitative approach by interviewing prisoners, corrections officers, and other related parties, in two different locations. In conclusion, this research wraps two important points, first, sexual need as a right finds its justification derived from right to privacy and family life, right to humane treatment, and right to health and proper living. Second, there is a need for the state to arrange a mechanism in fulfiling prisoner’s sexual need based on human rights norms consideration.